Large Magnetovolume Effect Induced by Embedding Ferromagnetic Clusters into Antiferromagnetic Matrix of Cobaltite Perovskite. Issue 27 (8th May 2017) - Miao, Ping; Lin, Xiaohuan; Koda, Akihiro; Lee, Sanghyun; Ishikawa, Yoshihisa; Torii, Shuki; Yonemura, Masao; Mochiku, Takashi; Sagayama, Hajime; Itoh, Shinichi; Ikeda, Kazutaka; Otomo, Toshiya; et al.
Abstract : Materials that show negative thermal expansion (NTE) have significant industrial merit because they can be used to fabricate composites whose dimensions remain invariant upon heating. In some materials, NTE is concomitant with the spontaneous magnetization due to the magnetovolume effect (MVE). Here the authors report a new class of MVE material; namely, a layered perovskite PrBaCo2 O5.5+ x (0 ≤ x ≤ 0.41), in which strong NTE [β ≈ −3.6 × 10 −5 K −1 (90–110 K) at x = 0.24] is triggered by embedding ferromagnetic (F) clusters into the antiferromagnetic (AF) matrix. The strongest MVE is found near the boundary between F and AF phases in the phase diagram, indicating the essential role of competition between the F‐clusters and the AF‐matrix. Furthermore, the MVE is not limited to the PrBaCo2 O5.5+ x but is also observed in the NdBaCo2 O5.5+ x . The present study provides a new approach to obtaining MVE and offers a path to the design of NTE materials. Abstract : A new class of negative thermal expansion (NTE) material is discovered, in which the NTE is induced by a new mechanism. Namely, the layered perovskite PrBaCo 2 O 5.5+x (0 ≤ x ≤ 0.41) exhibits a strong NTE when embedding (F) clusters into the (AF) matrix, where the competition between the F and AF phases plays the essential role.